Analysis of luminescence method for determination of Cd₁₋xZnxTe composition - Glinchuk, K.D.; Litovchenko, N.M.; Prokhorovich, A.V.; Strilchuk, O.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
A detailed analysis of the method for determination of Cd₁₋xZnxTe composition x from measurements of 4.2 K peak position of the emission band induced by annihilation of excitons bound with neutral shallow acceptors is given. Found are the conditions fulfillment of which permits to obtain reliable x values by the above luminescence method.